Making Provision for First-Hand Nature-Based Learning Within a Botanic Garden - MacQuarrie, Sarah; Nugent, Clare (Frontiers in Education, 2022)
This paper reports on a study of nature play in two botanic gardens where there are normally strict rules about touching and handling plants. Features of nature-based play and learning are presented and available evidence is drawn together as the basis for a series of nature interventions trialled within a botanic garden. Data were recorded using three methods: time-sampled observations, annotation of intervention-specific maps and follow-up questionnaires completed by adults. Findings evidence that the nature play can be fostered in botanic gardens and it is advantageous to support such interaction by carefully promoting play in designated spaces. Visitors embraced play opportunities and valued the freedom to behave and investigate in ways that are a departure from tradition and given the lack of research regarding such play and learning environments such findings ought to be noted as addressing a gap within the literature. Findings are relevant to comparable sites that encounter challenges when balancing differing agendas that include nature conservation with visitor experience. Botanic gardens can offer a useful route to examine conservation, environmental understanding and stewardship with the youngest members of society as nature play experiences are first-hand and locally relevant.